Study on the development of liquid extract of cardiotonic action - O. S. Kukhtenko; N. Y. Bevz; Ie. V. Gladukh; H. P. Kukhtenko (The State Expert Center of the Ministry of Health of Ukraine, 2019)
At the Department of Industrial Pharmacy of the National University of Pharmacy, a complex cardiotonic action extract containing extracts of Crataegus охуaсanta fruits, Leonurus cardiaca herb, Melissa officinalis herb and Humulus lupulus seedballs in equals proportions is being developed. The purpose of work was to determine the quantitative yield of biologically active substances, depending on the degree of depletion of medicinal plant raw materials extractant. Each medicinal plant raw material used in obtaining the extract was tested for compliance with the incoming normative documents and crushed. Percolation was performed using a laboratory percolator. As an extractant, 70% ethyl alcohol was used. The extraction process was carried out till obtaining a total extract of DER 1:10. For each separately collected sample of the liquid extract, the dry residue was determined using the Sartorius MA150C moisture analyzer (Germany). The extraction process was monitored by quantifying the polyphenolic compounds in extracts obtained in portions with DER step 1: 1 spectrophotometrically on the Evolution 60s spectrophotometer (Thermo Fisher Scientific, USA). The maximum yield of polyphenolic compounds is observed from Humulus lupulus. The smallest amount of polyphenolic compounds is extracted from the grass of Melissa officinalis and Crataegus oxyacanta. This trend is maintained for all variants of the ratio of raw materials/extractant. According to the physical and chemical research, the presence of polyphenolic nature substances in the composition of the extractions of the investigated medicinal plant material and the total extract has been confirmed. According to the results of the study, it was determined that the maximum amount of polyphenolic compounds is removed from the following medicinal plant material - Humulus lupulus. The results correlate with earlier studies to determine the multiplicity of extraction by dry residue in the extract and extractions of individual plant materials.